Dose-response of Fricke- and PAGAT-dosimetry gels in kilovoltage and megavoltage photon beams: Impact of LET on sensitivity. (April 2021) - Vedelago, José; Chacón, David; Romero, Marcelo; Venencia, Daniel; Mattea, Facundo; Valente, Mauro
Highlights: Fricke and PAGAT gel dosimeters sensitivities were evaluated in photon beams. Both dosimeters showed quantifiable response for kV and MV photon beams. Optical absorbance and MRI can measure dose-response for kV photons. Response at 44 kV was found to be on average 0.65 times the response at 6 MV. Differences were explained in terms of radiation chemical yields variations. Abstract: Purpose: Dosimetry of ionizing radiation quantifies the energy deposited by an incident beam to the medium. This study presents the relative response of two types of gel dosimeters describing their differences by estimating radiation chemical yields produced in water radiolysis. Methods: Two types of gel dosimeter were used, namely an acid ferrous ion solution infused with xylenol orange known as Fricke gel and a polymer gel based on acrylamide and N, N'-methylenebis(acrylamide) known as PAGAT. Samples were irradiated using two photon beam energies, one from a conventional X-ray tube operated at 44 kV and the other one from a LINAC operated at 6 MV. The dosimeters were analyzed by optical absorbance and magnetic resonance imaging. Additionally, the linear energy transfer of each beam was calculated using Monte Carlo simulations for further estimation of the radiation chemical yields produced during water radiolysis. Results: Obtained results for both gel dosimeters indicate that their response at 44 kV and 6 MV are different, regardless of the read-out technique. On average, the sensitivity at 44 kV was found to be 65 % of the response at 6 MV. The calculated radiation chemical yields are in agreement with the observed experimental results. Conclusions: The main reason for the difference in the response of the dosimeters may be related to the linear energy transfer of each photon beam, which varies the production of primary chemical species during water radiolysis.